Diabetes and experimental pregnancy in rats: Course of maternal blood glucose levels and its repercussions on the blood glucose levels and pancreas of newborn pups - Rudge, M. V.C. [UNESP]; Calderon, I. M.P. [UNESP]; Ramos, M. D. [UNESP]; Rodrigues, M. A.M. [UNESP] (My University, 1995)
The objective of the present investigation was to determine the course of maternal blood glucose levels in pregnant rats and its repercussions on the glucose levels and pancreas of their newborn pups. Diabetes was induced by alloxan (42 mg/kg body weight) and streptozotocin (40 mg/kg). Sixty-two pregnant Wistar rats weighing 180 to 250 g were divided into a control group and two groups with moderate (120 to 200 mg/dl glucose) and severe diabetes (greater than 200 mg/dl glucose), respectively. Blood glucose levels were measured in the dams on the 1st, 14th, and 21st days of pregnancy and in the pups at birth. The results were pooled for each litter. The fetal pancreases were removed after cesarian section performed on the 21st day of pregnancy, pooled for each litter and processed for histopathologic examination by light microscopy. Maternal blood glucose levels were significantly increased compared with the first day of pregnancy in both normal and diabetic rats starting on the 14th day of pregnancy. Fetal blood glucose levels correlated with maternal levels. The histopathologic changes characterized by vacuolization and basophilia of the cytoplasm of endocrine pancreas of newborn pups from dams with moderate or severe diabetes suggested pancreatic hyperactivity.
Keywords: diabetes and pregnancy; maternal blood glucose; pregnancy in rats